Physician Workflow in Two Distinctive Emergency Departments: An Observational Study - Patel, Vimla L.; Denton, Courtney A.; Soni, Hiral C.; Kannampallil, Thomas G.; Traub, Stephen J.; Shapiro, Jason S. (Applied Clinical Informatics, 2021)
Objectives We characterize physician workflow in two distinctive emergency departments (ED). Physician practices mediated by electronic health records (EHR) are explored within the context of organizational complexity for the delivery of care.Methods Two urban clinical sites, including an academic teaching ED, were selected. Fourteen physicians were recruited. Overall, 62 hours of direct clinical observations were conducted characterizing clinical activities (EHR use, team communication, and patient care). Data were analyzed using qualitative open-coding techniques and descriptive statistics. Timeline belts were used to represent temporal events.Results At site 1, physicians, engaged in more team communication, followed by direct patient care. Although physicians spent 61% of their clinical time at workstations, only 25% was spent on the EHR, primarily for clinical documentation and review. Site 2 physicians engaged primarily in direct patient care spending 52% of their time at a workstation, and 31% dedicated to EHRs, focused on chart review. At site 1, physicians showed nonlinear complex workflow patterns with a greater frequency of multitasking and interruptions, resulting in workflow fragmentation. In comparison, at site 2, a less complex environment with a unique patient assignment system, resulting in a more linear workflow pattern.Conclusion The nature of the clinical practice and EHR-mediated workflow reflects the ED work practices. Physicians in more complex organizations may be less efficient because of the fragmented workflow. However, these effects can be mitigated by effort distribution through team communication, which affords inherent safety checks.
Keywords: clinical workflow; emergency medicine; electronic health records; complexity; patient safety